Inhibition of glycine transporter‐1 reduces cue‐induced nicotine‐seeking, but does not promote extinction of conditioned nicotine cue responding in the rat. (14th March 2013) - Cervo, Luigi; Di Clemente, Angelo; Orrù, Alessandro; Moro, Federico; Cassina, Chiara; Pich, Emilio Merlo; Corsi, Mauro; Gozzi, Alessandro; Bifone, Angelo
Abstract Pharmacological stimulation of N‐methyl‐D‐aspartate receptors (NMDAr) could enhance the outcome of cue‐exposure therapy for smoking cessation. NMDAr stimulation can be achieved by increasing pharmacologically the synaptic levels of glycine, a necessary co‐agonist. Here, we evaluate the effects of SSR504734, a selective inhibitor of glycine type I transporter (GlyT1) in an extinction‐reinstatement procedure inducing robust and lasting nicotine‐seeking behavior in rats. Male Wistar rats were trained to associate discriminative stimuli (SDs) with the availability of nicotine (0.03 mg/kg/65 μL/2 second/infusion) or sucrose (45‐mg pellet) versus non‐reward in two‐lever operant cages. Reinforced response was followed by cue signaling 20‐second time‐out (CSs). Once the training criterion was met, rats underwent extinction of lever presses, in the absence of reinforcers, SDs and CSs. Re‐exposure to nicotine or sucrose SD+/CS+, but not non‐reward SD−/CS−, revived responding at the previously reinforced lever. Acute pre‐treatment with SSR504734 (10 mg/kg i.p.) reduced nicotine‐seeking but not sucrose‐seeking behavior without influencing rats' locomotor activity. Sub‐chronic treatment (10 mg/kg i.p. for 5 days) during daily exposure to SD+/CS+ reduced nicotine‐seeking; however, this effect was transient, with return to SD+/CS+ responding at 72 hours. Full recovery to SD+/CS+ responding was observed after 1 month suggesting that SSR504734 sub‐acute treatment did not engage the long‐term plasticity mechanisms probably involved in nicotine‐seeking. In conclusion, GlyT1‐inhibitors might offer a therapeutic opportunity for acute cue‐controlled nicotine‐seeking, but the lack of persistent effects of the sub‐chronic treatment associated with nicotine cues exposure suggests that short‐term administration of GlyT1‐inhibitor SSR504734 is not sufficient to promote extinction of nicotine‐cue conditioned responding.